Evaluating Students' Performance in Consonant Phoneme Identification within Word Structures - Sharma, Lok Raj (International Research Journal of MMC, 2024)
The prime objectives of this article are to evaluate the bachelor level first year major English students’ performance in consonant sound identification within word structures, and examine the effectiveness of an intuitive-imitative approach in teaching consonant phonemes of the spellings. To attain these objectives, the researchers employed the one-group pretest posttest research design in which 200 phoneme recognition test items as data collection tools regarding the consonant sounds of English were administered to 30 students at Makawanpur Multiple Campus, Hetauda, Nepal in 2023 before and after teaching them the sounds through the intuitive-imitative approach for 30 teaching periods. Population being low, this study involved the census for collecting data. After observing their performance in consonant phoneme identification, it was found that their performance was bad at identifying the phonemes of the spelling's “g” in “Genre”, “c” in “Cello”, “th” in “Thailand”, etc. Their performance was not so good at identifying the phonemes of the spellings “j” in “Join”, “y” in “Yak”, etc. Their performance was satisfactory in identifying the phonemes of the spelling's “g” in “Gene”, “g” in “Gem”, “n” in “Donkey”, etc. Similarly, they were good at identifying the phonemes of spelling “p” in “Punch”, “b” in “Boat’, “k’ in “Book”, etc. A related samples Wilcoxon signed rank test value (p  .05) implies that there was a significant difference in the median scores of the posttest scores and the pretest scores of the students. It suggests that the intuitive-imitative approach was an effective method of teaching sounds. This article is significant in a phonological process and pronunciation, resulting in phonemic awareness.